Efektivitas Model Pembelajaran Kooperatif Talking Stick terhadap Peningkatan Motivasi Belajar - Alvia Sabrina; Ayi Sobarna; Haditsa Qurani Nurhakim (Jurnal Riset Pendidikan Agama Islam, 2024)
Abstract. The aim of this research is to determine the level of student learning motivation in Islamic Religious Education lessons on historical material, namely the Khulafaurrasyidin Struggle, by applying the Cooperative Talking Stick learning model, as well as to determine the differences between the learning motivation of the two classes, namely the experimental class and the control class. This research uses a quantitative approach with a quasi-experimental method with a nonequivalet control group design. The results of the research show 1) The learning motivation of students in the control class did not experience a high increase in learning motivation but was only stuck at a moderate level. 2) Students' learning motivation in the experimental class experienced a very significant increase and reached a high level after being treated with the Talking Stick cooperative learning model. 3) The effectiveness of student learning motivation results between the experimental class and the control class can be proven by t-test analysis, obtained t value > t table (15.492 > 2.002), so it can be concluded that H_o is rejected and H_i is accepted, meaning there is an average difference between the post-test experimental class and post-test control class. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui tingkat motivasi belajar siswa pada pelajaran Pendidikan Agama Islam materi sejarah yaitu Perjuangan Khulafaurrasyidin dengan menerapkan model pembelajaran Kooperatif Talking Stick, serta mengetahui perbedaan dari antara motivasi belajar dari dua kelas yaitu kelas eksperimen dan kelas kontrol. Penelitan ini menggunakan pendekatan kuantitatif dengan metode quasi eksperimen dengan bentuk desain Nonequivalet kontrol Group Design. Hasil penelitian menunjukan 1) Motivasi belajar siswa di kelas kontrol tidak mengalami peningkatan motivasi belajar yang tinggi namun hanya stuck pada taraf yang sedang. 2) Motivasi belajar siswa di kelas eksperimen mengalami peningkatan yang sangat signifikan dan mencapai taraf tinggi setelah diberikan perlakuan model pembelajaran kooperatif talking Stick. 3) Efektivitas hasil motivasi belajar siswa antara kelas eksperimen dan kelas kontrol dapat dibuktikan dengan analisis t-test, diperoleh nilai t hitung > t tabel (15,492 > 2,002), maka dapat disimpulkan  ditolak dan  diterima berati terdapat perbedaan rata rata antara post-test kelas eksperimen dan post-test kelas kontrol.